PSYCHOLOGICAL FACTORS OF INNOVATIVENESS AMONG NOMADIC MICRO-ENTREPRENEURS FOR ACHIEVING BUSINESS GROWTH - TAGHIZADEH, Seyedeh Khadijeh; RAHMAN, Syed Abidur; AHMAD, Noor Hazlina; RAMAYAH, Thurasamy (VERSLAS: TEORIJA IR PRAKTIKA, 2016)
The objective of this paper is to explore the psychological factors of innovativeness that drives nomadic micro entrepreneurs’ (MEs) in enhancing their business growth in Malaysia. Nomadic micro entrepreneurs refer to those who regularly change the location of their business. To meet the research objective, the current study carried out in-depth interviews among the Nomadic MEs operating their business in Northern region, Malaysia. Twenty Nomadic MEs were interviewed on voluntary basis. Thematic analysis was conducted to identify the recurring themes that delineate psychological factors that may influence innovativeness. Interestingly, the findings revealed that the innovativeness of Nomadic MEs is influenced by four psychological characteristics namely sense of curiosity, interest, risk taking, and risk avoidance. The contribution of this study lies in the identification of four substantial psychological factors that act as a foundation for innovativeness among nomadic micro entrepreneurs’ (MEs) in enhancing their business growth.